Behavioral and biological divergence in monozygotic twin pairs discordant for autism phenotypes: A systematic review - Lynnea Myers; Pei‐Yin Pan; Karl Lundin Remnélius; Janina Neufeld; Peter B. Marschik; Ulf Jonsson; Sven Bölte (Wiley, 2021)
Abstract Background Non‐shared environment (NSE) effects account for around one‐third of the etiology of autism spectrum disorder (ASD). However, the knowledge of mechanisms and phenotypic profiles associated with NSE in ASD is scarce. Methods A systematic search was conducted using Embase, MEDLINE, and PsycINFO for studies published in English between 1990 and August 2020 using co‐twin control design to compare behavioral and biological phenotypes among monozygotic (MZ) twin pairs concordant/discordant for ASD, clinical autism symptoms, or autistic traits. Risk of bias was assessed through a modified Newcastle-Ottawa Scale. Results Twenty six articles were included. Differential DNA methylation and gene expression were found among ASD discordant twins; however, genetic results were inconsistent. Neurological disorders and early medical events were associated with ASD and autistic traits, while no within pair differences were found for minor physical anomalies or head circumference. Structural and functional brain imaging studies and research on social and other cognitive/behavioral functions were inconclusive. Risk of bias assessment found that all studies used the same exposure (or outcome) measures to collect data for participants and most used either secure health‐related records or structured interviews for ascertainment of exposure; however, only a handful of studies representative of the population from which they were drawn. Formal assessment of risk of publication bias (i.e., funnel plot) was not possible. Conclusions Our results suggest that NSE in ASD could be associated with heterogeneous postzygotic genetic mechanisms and manifest as a range of biological and behavioral phenotypes. Extant findings were limited by relatively few studies, small sample sizes, and methodological diversity. More research is needed on co‐occurring biological and behavioral phenotypes using a consistent format for designing, analyzing, and reporting MZ ASD discordant twin studies in order to further examine the role of NSE in the etiology of ASD.